Design, Manufacture, and In vivo Testing of a Tissue Scaffold for Permanent Female Sterilization by Tubal Occlusion. (15th January 2018) - Divakar, Prajan; Caruso, Isabella; Moodie, Karen L.; Theiler, Regan N.; Hoopes, P. Jack; Wegst, Ulrike G.K.
ABSTRACT: Current FDA-approved permanent female sterilization procedures are invasive and/or require the implantation of non-biodegradable materials. These techniques pose risks and complications, such as device migration, fracture, and tubal perforation. We propose a safe, non-invasive biodegradable tissue scaffold to effectively occlude the Fallopian tubes within 30 days of implantation. Specifically, the Fallopian tubes are mechanically de-epithelialized, and a tissue scaffold is placed into each tube. It is anticipated that this procedure can be performed in less than 30 minutes by an experienced obstetrics and gynaecology practitioner. Advantages of this method include the use of a fully bio-resorbable polymer, low costs, lower risks, and the lack of general anaesthesia. The scaffold devices are freeze-cast allowing for the custom-design of structural, mechanical, and chemical cues through material composition, processing parameters, and functionalization. The performance of the biomaterial and de-epithelialization procedure was tested in an in vivo rat uterine horn model. The scaffold response and tissue-biomaterial interactions were characterized microscopically post-implantation. Overall, the study resulted in the successful fabrication of resilient, easy-to-handle devices with an anisotropic scaffold architecture that encouraged rapid bio-integration through notable angiogenesis, cell infiltration, and native collagen deposition. Successful tubal occlusion was demonstrated at 30 days, revealing the great promise of a sterilization biomaterial.